Role of Lipid Rafts in Pathogen-Host Interaction - A Mini Review - Kulkarni, Rakesh; Wiemer, Erik A. C.; Chang, Wen (Frontiers in Immunology, 2022)
Lipid rafts, also known as microdomains, are important components of cell membranes and are enriched in cholesterol, glycophospholipids and receptors. They are involved in various essential cellular processes, including endocytosis, exocytosis and cellular signaling. Receptors are concentrated at lipid rafts, through which cellular signaling can be transmitted. Pathogens exploit these signaling mechanisms to enter cells, proliferate and egress. However, lipid rafts also play an important role in initiating antimicrobial responses by sensing pathogens via clustered pathogen-sensing receptors and triggering downstream signaling events such as programmed cell death or cytokine production for pathogen clearance. In this review, we discuss how both host and pathogens use lipid rafts and associated proteins in an arms race to survive. Special attention is given to the involvement of the major vault protein, the main constituent of a ribonucleoprotein complex, which is enriched in lipid rafts upon infection with vaccinia virus.